Internal consistency and factorial structure of the Beck Hopelessness Scale among Mexican students - Córdova Osnaya, Martha (2011)
The Beck Hopelessness Scale was applied in a sample of 971 male and female students, chosen at random sampling from Mexico City, with an average age of 16.75 years. Results were compared to those reported by Beck, Weissman, Lester and Trexler (1974). Results showed adequate reliability (≥ 0.70) in the total sample by gender. Factorial structure matched only in the Affective factor as reported by Beck et al. (1974) with respect to the total sample. Differences in saturation and factorial structure in both sexes were observed. It was concluded that the factor structure of Beck Hopelessness Scale registers different factor structure in the total sample, according to sex.